POTENSI OMEGA-3 BULU BABI (SEA URCHIN) DALAM KONTROL PROGRESIVITAS DEMENSIA ALZHEIMER - Arina Windri Rivarti (Faculty of Medicine Universitas Mataram, 2022)
With the increasing prevalence of Alzheimer's dementia and the lack of effectiveness of existing drugs in inhibiting the progression of the disease, the investigation of new drug candidates will continue. Omega-3 fatty acids, especially docosahexaenoic acid (DHA), are compounds that can be used as drug candidates for this purpose. Recent scientific evidence, both from epidemiological studies and preclinical trials in experimental animals, shows the potential of these compounds in maintaining cognitive function and inhibiting the progression of Alzheimer's dementia through various mechanisms, including anti-inflammatory, anti-amyloidogenic, and brain neuroplasticity. These compounds are contained in various marine organisms, including sea urchins. Given the wide availability of marine life on the coast and its ability to biosynthesis of omega-3 fatty acids, this marine biota can be considered as the main source of omega-3 in the development of omega-3 as a drug for the protection of cognitive function in Alzheimer's disease dementia.